The effect of the relationship of some variables to mathematics teachers and its relationship to teaching - Sadeq Ghali, Asma (International Journal of Psychosocial Rehabilitation, 2020)
In order to properly situate the problem in its context, attention will first be drawn to a definition of motivation and its impact on student success. Second, we will follow up on the impact that living in a disadvantaged environment can have on student motivation. Finally, the relationship between the teacher and the student will be put forward so as to understand the importance it can take as a protective factor in a school career. This first chapter will end with the formulation of the general objective.